Juvenile post-adjudication dispositions - Kowalski, Gregory S. (American journal of criminal justice, 1982)
Six socio-demographic and graphic and diagnostic and evaluation center (D&E) variables which influence juvenile post-adjudication disposition into one of two treatment modalities, group home or institution, are examined. Data employed in this study were gathered from completed case history records for 133 randomly sampled male juveniles processed over a six-month period by a department of youth services (DYS) facility in a southern state. Discriminant function analysis was used to determine statistical distinction between the two disposition groups. The discriminant analysis yielded five variables of statistical significance (p<-.001, canonical r =−40) which included a D&E behavior measure, age, number of past offenses, full scale IQ score, and seriousness of admitting offense. Eighty-one percent of all cases were correctly classified using the selected socio-demographic and D&E variables. Race was not found to be significant in the decision-making process at this level.